Citizenship status and engagement in HIV care: an observational cohort study to assess the association between reporting a national ID number and retention in public-sector HIV care in Johannesburg, South Africa. Issue 1 (24th January 2017) - Shearer, Kate; Clouse, Kate; Meyer-Rath, Gesine; MacLeod, William; Maskew, Mhairi; Sanne, Ian; Long, Lawrence; Fox, Matthew P
Abstract : Objective: In many resource-limited settings, people from rural areas migrate to urban hubs in search of work. Thus, urban public-sector HIV clinics in South Africa (SA) often cater to both local residents and patients from other provinces and/or countries. The objective of this analysis was to compare programmatic treatment outcomes by citizenship status in an urban clinic in SA. Setting: An urban public-sector HIV treatment facility in Johannesburg, SA. Participants: We included all antiretroviral therapy (ART)-naïve, non-pregnant patients who initiated standard first-line treatment from January 2008 to December 2013. 12 219 patients were included and 59.5% were women. Primary outcome measure: Patients were followed from ART initiation until death, transfer, loss to follow-up (LTF), or data set closure. We describe attrition (mortality and LTF) stratified by SA citizenship status (confirmed SA citizens (with national ID number), unconfirmed SA citizens (no ID), and foreign nationals) and model the risk of attrition using Cox proportional hazards regression. Results: 70% of included patients were confirmed SA citizens, 19% were unconfirmed SA citizens, and 11% were foreign nationals. Unconfirmed SA citizens were far more likely to die or become LTF than other patients. A similar proportion of foreign nationals (18.2%) and confirmed SA citizens (17.7%) had left care at 1 year compared with 47.0% of unconfirmed SA citizens (adjusted hazard ratio (aHR) unconfirmed SA vs confirmed SA: 2.68; 95% CI 2.42 to 2.97). By the end of follow-up, 75.5% of unconfirmed SA citizens had left care, approximately twice that of any other group. Conclusions: Unconfirmed SA citizens were more likely to drop out of care after ART initiation than other patients. Further research is needed to determine whether this observed attrition is representative of migration and/or self-transfer to another HIV clinic as such high rates of attrition pose challenges for the success of the national ART programme.